2020
DOI: 10.1248/bpb.b19-01091
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Inhibits Constitutive Airway Epithelial Sodium Channel Activation <i>in Vitro</i> and Modulates Downstream Pathogenesis <i>in Vivo</i>

Abstract: Epithelial sodium channel (ENaC) is an amiloride-sensitive sodium ion channel that is expressed in epithelial tissues. ENaC overexpression and/or hyperactivation in airway epithelial cells cause sodium overabsorption and dysregulated ciliary movement for mucus clearance; however, the agents that suppress constitutive airway ENaC activation are yet to be clinically available. Here, we focused on macrolides, which are widely used antibiotics that have many potential immunomodulatory effects. We examined whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Importantly, we used a much longer duration in our experiment, and it was expected to notice much more QT prolongation on the ECG and reduced conductance on Nav1.5. Differently, Fujikawa et al demonstrated that macrolide antibiotics suppress the airway epithelial sodium channels in vitro [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we used a much longer duration in our experiment, and it was expected to notice much more QT prolongation on the ECG and reduced conductance on Nav1.5. Differently, Fujikawa et al demonstrated that macrolide antibiotics suppress the airway epithelial sodium channels in vitro [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…CF patients have a higher prevalence of RSV and a higher viral load in bronchoalveolar lavage fluid (BALF) than non-CF patients (37). Moreover,~15-25% of CF patients with a respiratory viral infection also culture positive for a known CF bacterial pathogen (23,50,78). Coinfection with RSV and P. aeruginosa is associated with declines in pulmonary function and increased morbidity and mortality (28,53).…”
Section: Viral Lung Infections In Cfmentioning
confidence: 99%
“…29 34 One potential explanation is that beneficial effects of azithromycin in the airway unrelated to Pseudomonas outweighed the effects of increased P. aeruginosa burden, resulting in a disconnect between changes in lung function and airway infection. [35][36][37][38][39] Another potential explanation is that our study population, by design, was not naïve to inhaled tobramycin, and neither group (ie, azithromycin or placebo treated) had a significant increase in FEV 1 during inhaled tobramycin use. A diminishing effect on FEV 1 over subsequent cycles of inhaled tobramycin was reported in even the earliest clinical trials.…”
Section: Discussionmentioning
confidence: 96%
“…This did not occur in our trial, similar to what has been seen in studies of inhaled levofloxacin in CF and multiple inhaled antibiotics in non-CF bronchiectasis 30 35 . One potential explanation is that beneficial effects of azithromycin in the airway unrelated to pseudomonas outweighed the effects of increased Pa burden, resulting in a disconnect between changes in lung function and airway infection 36 40 . Another potential explanation is that our study population, by design, was not naïve to inhaled tobramycin, and neither group (i.e., azithromycin or placebo-treated) had a significant increase in FEV 1 during inhaled tobramycin use.…”
Section: Discussionmentioning
confidence: 99%